Hubungan Asupan Protein, Zat Besi, dan Vitamin C Dengan Kejadian Anemia pada Remaja Putri di Pondok Pesantren Darul Arqom Muhammadiyah Kalirejo Kabupaten Lampung Tengah Tahun 2024 - Anindia, Iren Iftia; Jayadi, Ajib; Dalimunthe, Nathasa Khalidha (Journal of Education Technology Information Social Sciences and Health, 2025)
The issue of anemia poses a significant risk to adolescents who are undergoing critical stages of growth and development. Anemia is defined as having hemoglobin (Hb) levels below 12 g/dL for females and below 13.5 g/dL for males. This condition is often linked to deficiencies in both macro and micronutrients, particularly in protein, iron, and vitamin C. The objective of this study was to explore the correlation between the intake of protein, iron, and vitamin C and the prevalence of anemia among adolescent girls at Darul Arqom Muhammadiyah Kalirejo Islamic Boarding School in Central Lampung Regency. A cross-sectional methodology was employed, focusing on grades 8 and 9, with a sample of 90 adolescent girls aged 12 to 15 years. The final sample consisted of 52 participants, determined using Slovin's sampling formula. Data were collected through a simple random sampling technique. The findings revealed a significant association between protein intake (p = 0.047) and iron intake (p = 0.008) with the occurrence of anemia; however, no significant relationship was found between vitamin C intake (p = 1.000) and anemia. It is recommended that both the boarding school and the adolescent girls themselves place greater emphasis on their dietary intake, especially on protein and iron intake.